Maantieteen opettajien näkemyksiä geomediasta ja geomediaopetuksesta [Geography teachers’ views on geomedia and geomedia education] - Hynynen Laura; Nylén Tua; Hirvensalo Virpi; Lammi Papu; Muukkonen Petteri (Suomen Maantieteellinen Seura, 2025)
While geomedia is a new concept in Finnish curricula, it merely describes geographical methods and data that have always been central in geography education. In this study, we interviewed geography teachers on 1) how they understand the concept of geomedia, 2) what is the role of geomedia in their students’ everyday lives and how that is reflected in the school education, and 3) what is the impact of geomedia education for geography education in general and for the society. The interviewed teachers work with pupils from ages 7 to 19. The results show, for example, that most teachers consider geomedia as a useful hypernym at the curriculum level, but understanding of the concept is limited and few teachers utilize the term in the classroom. Outside the classroom pupils are mainly exposed to visual forms of geomedia and would need stronger skills to examine it critically. The teachers agree that geomedia education forms the basis of methodological geography skills and supports geographical thinking. Finally, geomedia education provides the pupils with skills to use geomedia in their everyday lives and to acquire many relevant skills in the future.